IMPLEMENTASI KEBIJAKAN REFORMASI BIROKRASI BERDAMPAK DI KABUPATEN TULUNGAGUNG - Iswanto, Denny (Jurnal Inovasi Daerah, 2024)
Bureaucratic Reform has become a crucial issue in facing challenges and changes in the modern government order. Every government entity, both ministries, institutions, and regions, is required to implement the bureaucratic reform agenda to improve the competence of ASN with a professional work culture that has high integrity, effective performance, free and protected from various bureaucratic pathologies and avoid harmful practices. This study aims to analyze the implementation of bureaucratic reform in Tulungagung Regency. This research applies qualitative methods using in-depth interviews, observation, and document analysis as data collection techniques. The focus of this research is to use the theory of policy implementation from Edward III, which sees policy implementation from four indicators: communication, resources, disposition and bureaucratic structure. The results showed that there was a positive development in the implementation of RB based on the Bureaucratic Reform Index and the ASN professionalism index in Tulungagung Regency. However, there are still many obstacles encountered such as policies that have not been integrated, the low quality of human resources, and administrative problems in public services so that acceleration of RB transformation is needed. This research is expected to provide relevant and evidence-based policy recommendations to support the government's efforts to improve the efficiency and quality of public services through bureaucratic reform.